2015
DOI: 10.1111/1752-1688.12314
|View full text |Cite
|
Sign up to set email alerts
|

A Water Yield‐Oriented Practical Approach for Multifunctional Forest Management and its Application in Dryland Regions of China

Abstract: Mountainous forest areas are vitally important for water supply in dryland regions which suffer from high erosion risk and severe water shortage. Massive afforestation, mainly for erosion control, may reduce the water yield and threaten local water supply security. Moreover, many over-dense forests due to a strict logging ban policy have produced remarkably negative impacts for both forests (e.g., low timber quality, restricted natural regeneration, and high stand instability) and water yield. To satisfy the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In this research, the main forests are dominated by pines. Based on the previous studies, the conifer forests consumed more water than the other forest type [24]- [25]. A similar result was also found in another study as reported in [26] when a paired catchment was used.…”
Section: Annual Water Yield With Different Pine Forest Covers 1) Psupporting
confidence: 86%
See 1 more Smart Citation
“…In this research, the main forests are dominated by pines. Based on the previous studies, the conifer forests consumed more water than the other forest type [24]- [25]. A similar result was also found in another study as reported in [26] when a paired catchment was used.…”
Section: Annual Water Yield With Different Pine Forest Covers 1) Psupporting
confidence: 86%
“…They found that evapotranspiration was not only affected by climate factors but also depend on vegetation parameters including LAI. The higher value of LAI may cause a lower water yield [25]. In term of LAI, the evapotranspiration depends on solar radiation or the length of seasonal transpiration, stand density, and soil and water content [27], [33]- [34].…”
Section: Annual Water Yield With Different Pine Forest Covers 1) Pmentioning
confidence: 99%
“…converted all 6867 ha of rice fields to dryland crops [46]. In addition the JAPEWP program initiated in 2009 is restoring forest landscapes in key source water areas to sustain and improve ES related to water yield and purification, as moderate forest cover can have positive effects on these [3,47]. A total of 1.1 billion yuan has been invested to build 66,666 ha of water protection forest within the key areas of Miyun and Guanting Reservoir Catchment of Hebei Province [48].…”
Section: Study Areamentioning
confidence: 99%
“…The last paper in this collection by Wang et al . () addresses issues related to tradeoffs between water yield and growing plantation forests in the mountainous areas in arid northern China. The authors design an “ideal” stand structure for multifunctional forests (MFF) and determine its key parameters by integrating existing forest hydrology knowledge and experience.…”
Section: Overview Of Featured Collectionmentioning
confidence: 99%